2020
DOI: 10.3390/ijms21197401
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 Deficiency Attenuates DNFB-Induced Contact Hypersensitivity through Skewed Polarization towards M2 Phenotype in Macrophages

Abstract: CX3CL1 can function as both an adhesion molecule and a chemokine for CX3CR1+ cells, such as T cells, monocytes, and NK cells. Recent studies have demonstrated that CX3CL1–CX3CR1 interaction is associated with the development of various inflammatory skin diseases. In this study, we examined CX3CR1 involvement in 2,4-dinitrofluorobenzene (DNFB)-induced contact hypersensitivity using CX3CR1−/− mice. Ear swelling and dermal edema were attenuated after DNFB challenge in CX3CR1−/− mice. Expression of TNF-α, IL-6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Besides, M1 pro-inflammatory macrophages (glycolytic phenotype) ( 122 , 123 ) are also involved in asthma reactions. Interestingly, a study in a mouse model of 2,4-dinitrofluorobenzene-induced contact hypersensitivity demonstrated that M2 macrophages protected from local Th2 responses ( 124 ). These findings demonstrated that APCs might show different metabolic phenotypes in different allergic responses and further affect allergic reactions.…”
Section: Relevance Of Immune Metabolism For Allergic Diseasesmentioning
confidence: 99%
“…Besides, M1 pro-inflammatory macrophages (glycolytic phenotype) ( 122 , 123 ) are also involved in asthma reactions. Interestingly, a study in a mouse model of 2,4-dinitrofluorobenzene-induced contact hypersensitivity demonstrated that M2 macrophages protected from local Th2 responses ( 124 ). These findings demonstrated that APCs might show different metabolic phenotypes in different allergic responses and further affect allergic reactions.…”
Section: Relevance Of Immune Metabolism For Allergic Diseasesmentioning
confidence: 99%
“…For example, arginase-1 deficiency in lysozyme M (LysM) + cells including monocytes and macrophages resulted in exacerbation of CHS through upregulated inducible nitric oxide synthase (iNOS) expression [20]. Consistently, we recently reported that CHS in CX3C chemokine receptor 1 (CX3CR1)-deficient mice was attenuated with increased expression of arginase-1, which is a representative M2 macrophage marker [21]. Furthermore, dermal macrophage depletion in wild type (WT) mice before elicitation phase suppressed CHS, suggesting important roles of macrophages in CHS.…”
Section: Role Of Macrophages In Atopic Dermatitis and Contact Hypersensitivitymentioning
confidence: 81%
“…In general, M2 macrophages suppress Th1 responses, and skewed polarization towards M2 of macrophages in the lesion of contact dermatitis attenuates the inflammation [14]. CXCR1 deficiency reduces the expression of markers of M1 macrophage in the mouse models of contact dermatitis [15]. However, other mouse studies suggested the importance of M2 macrophages in the pathogenesis of contact dermatitis.…”
Section: Contact Dermatitismentioning
confidence: 99%